The Implementation of Take And Give Learning Methods With Portfolios To Improve The Biology Learning Outcomes Of Class II Students At SMA Pembangunan Bengkulu City - Eka Nurdianty Anwar (Perkumpulan Dosen Muda (PDM) Bengkulu, 2020)
This study aims to improve social studies learning outcomes using the portfolio study method of class VI students of SMA Pembangunan Kota Bengkulu. This research took place in two cycles. The instruments used were observation sheets, test questions. Data were analyzed qualitatIIely and quantitatIIely. The efficiency indicator of this study is that if at least 70% of students have reached KKM, 70 and the average class experience increases every cycle. The results of the study show that the use of the stages of the portfolio study method that is identifying problems, selecting problems to be studied, gathering information, making portfolio classes, presenting portfolios, hearing opinions and making conclusions can improve Biologi learning outcomes. The cognitIIe Biologi learning outcomes (tests) in the first cycle increased to 70.28% and the cycle II increased again to 91.90%. The percentage of cognitIIe domain CIIics learning outcomes (products) after the first cycle of action was shown to be 75.67%, and the cycle II action increased to 91.40%. Keywords: Portfolio, competence, Learning Outcomes